Quantitative cytochemical studies of acid secretagogue effects on the carbonic anhydrase activity of gastric parietal cell sections - Klaff, Leslie Joseph (Division of Endocrinology and Diabetology, 2017)
This thesis presents work designed to study the effects of acid secretagogues upon the parietal cell, in order to gain a greater understanding of their modes of action, and interaction and the role of circulating secretagogues in the mediation of parietal cell function, with the aim of increasing the understanding of the pathophysiology of the world-wide problem of peptic ulcer disease.